2020
DOI: 10.3390/genes11111322
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated dnmt3aa and dnmt3ab DNA Methyltransferase Genes Play Essential and Non-Overlapped Functions on Modulating Behavioral Control in Zebrafish

Abstract: DNA methylation plays several roles in regulating neuronal proliferation, differentiation, and physiological functions. The major de novo methyltransferase, DNMT3, controls the DNA methylation pattern in neurons according to environmental stimulations and behavioral regulations. Previous studies demonstrated that knockout of Dnmt3 induced mouse anxiety; however, controversial results showed that activation of Dnmt3 causes anxiolytic behavior. Thus, an alternative animal model to clarify Dnmt3 on modulating beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 112 publications
1
8
1
Order By: Relevance
“…This corroborated with our finding that chlorinated phosphates likely do not disrupt neurotransmitter activity. The present study also suggested an epigenetically driven FRC-induced neurotoxicity since dnmt3aa, a regulator of methylation of transcripts that drive neuronal development (Lai et al, 2020), was overexpressed by several FRCs. Such epigenetic regulation of FRC neurotoxicity was also reflected in a previous study, which showed that TDCIPP [Tris(1,phosphate], a chlorinated OPFRC that induced behavioral deficits in zebrafish, altered dnmt3aa transcript levels (Li et al, 2020).…”
Section: Neurotoxicity Of Frcssupporting
confidence: 64%
“…This corroborated with our finding that chlorinated phosphates likely do not disrupt neurotransmitter activity. The present study also suggested an epigenetically driven FRC-induced neurotoxicity since dnmt3aa, a regulator of methylation of transcripts that drive neuronal development (Lai et al, 2020), was overexpressed by several FRCs. Such epigenetic regulation of FRC neurotoxicity was also reflected in a previous study, which showed that TDCIPP [Tris(1,phosphate], a chlorinated OPFRC that induced behavioral deficits in zebrafish, altered dnmt3aa transcript levels (Li et al, 2020).…”
Section: Neurotoxicity Of Frcssupporting
confidence: 64%
“…It is worth noting that homozygous mutation of Dnmt3a in mice was fatal, whereas mutation of either dnmt3aa or dnmt3ab in zebrafish and tilapia was viable [28,29,70]. In this study, different spatial-temporal expression profiles of dnmt3aa and dnmt3ab, up-regulation of dnmt3ab in dnmt3aa −/− gonad and up-regulation of dnmt3aa in dnmt3ab −/− gonad were observed.…”
Section: The Function Of Dnmt3a (Dnmt3aa and Dnmt3ab) In Gonadal Development Of Vertebratesmentioning
confidence: 54%
“…These studies suggest that dnmt3aa and dnmt3ab may play important roles in gonadal development of fish, however, their detailed expression profiles during the sex determination and differentiation and gonadal development of teleost are unclear. Recently, some research groups reported the mutation of dnmt3aa and dnmt3ab in zebrafish, demonstrating their critical function on behavior regulation [28], temperature adaptation [29] and brain neural development [30]. Nevertheless, the roles of dnmt3aa and dnmt3ab in gonadal development of fish remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies on zebrafish have shown that the homozygous mutants of dnmt3aa or dnmt3ab are viable. Dnmt3aa and dnmt3ab are demonstrated to have essential and non-overlapped functions in modulating behavioral control, and dnmt3aa or dnmt3ab mutation fish display anxiety symptoms [ 30 ]. In addition, some groups have demonstrated the roles of dnmt3aa or dnmt3ab in regulating developmental thermal plasticity, and the phenotypic effects of dnmt3aa and dnmt3ab are additive [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that dnmt3aa and dnmt3ab may play important roles in the gonadal development of fish; however, their detailed expression profiles during the sex determination and differentiation and gonadal development of teleosts are unclear. Recently, some research groups reported the mutation of dnmt3aa and dnmt3ab in zebrafish, demonstrating their critical function on behavior regulation [ 30 ], temperature adaptation [ 31 ] and brain neural development [ 32 ]. Nevertheless, the roles of dnmt3aa and dnmt3ab in the gonadal development of fish remain unknown.…”
Section: Introductionmentioning
confidence: 99%